Operational Media: Cybernetics, Biopolitics and Postwar Education - Zoë Druick (FahrenHouse, 2020)
This article develops the concept of «operational media» to think through the deployment of utility/useful cinema in the context of cybernetically informed educational policy. The paper argues that cybernetic concepts of communication, feedback loops and homeostasis were central to the pragmatic installation of media at the center of postwar mass education. Links are made to the dominance of cybernetic ideas in postwar social science, including social psychology, sociobiology and behaviourism. A consideration of the UN's operational media allows for a reconsideration of the agency's communicative mandate as biopolitical and governmental. Educational policies influenced by the UN were doubly concerned with technologized classrooms: cybernetic ideas presented themselves as politically neutral, while offering efficiencies in the delivery of content. Cold war citizenship was thus conceived as a form of training that would pragmatically lead to the rebalancing of a volatile international situation. Carrefour de la vie (1949), made by Belgian filmmaker Henri Storck for the United Nations, is presented as an example of the centrality of mental health for citizenship training in postwar biopolitical regimes. In particular, the tension between the film's humanist and cybernetic strands are considered. Au Carrefour de la vie is considered as a transitional text, presenting a humanist story of childhood in postwar life that simultaneously prefigures the operation of a controlled society.